Health Risk Assessment of Pesticide Residues in Drinking Water of Upper Jhelum Region in Kashmir Valley-India by GC-MS/MS - M. Imran Ganaie; Ishrat Jan; Afshan Nabi Mayer; Alamgir A. Dar; Ishtiaq A. Mayer; Pervez Ahmed; Javid A. Sofi (International Journal of Analytical Chemistry, 2023)
Globally growing demand for agricultural and farm foods has more or less become dependent on chemical pesticides to maintain the supply chain, which undoubtedly boosts agricultural production. However, pesticides not only impact the target pests but cause hazard to human health. Pesticides are ubiquitous and can be found in almost every component of the environment. They can therefore impair human and biota health when present over the threshold level. The present study assessed the concentration of commonly used pesticides for agricultural purposes but get mixed in different sources of water, as such fifteen sampling sites along the upper Jhelum basin of Kashmir valley were chosen. For the analysis, 60 water samples were obtained from different water sources. Gas chromatography coupled with tandem mass spectrometry (GC-MS/MS) was used to determine pesticide residues in water samples. Pesticide residues from 10 of the 26 commonly used pesticides were detected in water samples. Difenoconazole had the highest concentration among the pesticides detected, with a mean concentration of 0.412 ± 0.424 μg/L ranging from 0.0 μg/L to 0.8196 μg/L. The target hazards quotient (THQ) was used to quantify the possible noncarcinogenic health risks associated with drinking pesticide-contaminated water. Only chlorpyrifos and quinalphos were detected >1 in RWS3 (1.6571), RWS4 (1.0285), RWS14 (1.2571), and RWS15 (1.2000) sample sites, implying that the drinking water poses a health risk to humans. Hence, pesticide hazards should be mitigated and rigorous monitoring is needed to reduce pesticide residues in drinking water.